On the Cult of Mary of Daniel Zieliński in the Light of the “Preface” to “Szata wzorzysta doskonałości” (1649) - Kaczor-Scheitler, Katarzyna (Respectus Philologicus, 2017)
This article presents the issues tackled in the “Preface” to Szata wzorzysta doskonałości, zakonnicę w oczach Boskich zdobiąca i wszelkim stanom ludzi żyć duchownie pragnących pożyteczna (The Patterned Robe of Perfection Worn by the Nun before the Eyes of God and Useful to All People Wishing to Lead a Spiritual Life) (Kraków 1649) by Daniel Zieliński, a Bernadine from Alwernia. Noteworthy in this work, orientated toward awakening prayer activity and promoting religious life, is the dedication to Mary, which constitutes an expression of the tribute to Mary made by the author as well as a testimony of his personal experience. The article shows that the “Preface” was written for the purpose of the cult of Mary and constitutes a testimony of the spirituality of the post-tridentine era. The author also reflected on the cult of Mary in Polish Catholicism, as manifested in the christenings, scapulars and rosaries, Marian Sodalities, the increasing role of sanctuaries to Mary (including Jasna Góra, Kalwaria Zebrzydowska) and the related pilgrimage movement. The cult of Mary was spread through prayer books, sermons, religious poetry and devotional books.
Keywords: Bernadine; Daniel Zieliński; dedication; cult of Mary; prayer books; sanctuaries to Mary; spirituality of the post-tridentine era